Resiko Investasi dan Pasar Modal Syariah dalam Analisis Kaidah Fikih - Muzan, Amrul; Amanda, Elisa; Andika, R. Yopan; Lutfi, Fadil (Program Studi Hukum Ekonomi Syariah, 2024)
This article discusses Islamic capital market risk analysis through a fiqh principles approach. The problem formulation includes the definition of investment, the concept of investment in Islamic law, the definition of sharia investment, as well as Islamic law's view of the sharia capital market. The research questions asked include: What is the concept of investment according to Islamic law? What is the difference between investment and speculation in sharia? What is the Islamic perspective on Islamic capital market risks?This research uses a descriptive analysis method with a normative juridical approach, which utilizes secondary data through document study and literature study. The findings show that the sharia capital market is based on the principles of halal, justice and avoidance of elements of usury, gharar and maisir. However, risks such as default on sukuk still exist and require mitigation through the application of the profit sharing principle. The Islamic capital market supports economic sustainability by complying with sharia principles that avoid market manipulation activities and interest-based transactions. This article concludes that the application of fiqh rules in the Islamic capital market not only increases fairness and transparency but also provides sustainable benefits for the economy and society at large.